Sustainability on the craft beer sector: Management improvements towards sustainable business and supply chain transparency: A case study on BARONA Brewing Company - Pinto, Mariana Rosa Anselmo (2021)
Craft beer has revolutionized the beer industry and market worldwide through diversification, innovation, authenticity, and tradition. As a result, these SMEs challenged the large breweries operating in a highly homogenized and consolidated market. Thus, addressing sustainability challenges in the growing craft beer sector is a strong recommendation. Therefore, this study has two main objectives. The first one is to understand how to improve sustainability in a Portuguese SME craft brewery named BARONA Brewing Company and implement sustainability practices into the business model. The second objective is more geared to operational level and practical improvements, looking to understand how this microbrewery can adapt to a transparent supply chain. A mixed methodology was used to provide value-added suggestions. Information about the current sustainability and supply chain activities and performance will be collected through direct field observation and semi-structured interviews. Results analysis showed that sustainability is not a focus for SMEs craft brewers. Even though it can be challenging to improve processes and measures to accomplish it, it is possible to include it in a business model by reducing resource consumption, minimizing waste, and focusing on efficient production. This will be cost-effective and make the company closer to a fully sustainable approach. However, when it comes to the supply chain transparency topic and the use of blockchain technology this is more challenging once it needs an investment of time and money, something some SME craft brewers may not be able to dispose of.